2010
DOI: 10.1111/j.1365-3040.2009.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger‐containing glycine‐rich RNA‐binding protein in Oryza sativa has an RNA chaperone activity under cold stress conditions

Abstract: The rice (Oryza sativa) genome harbours three genes encoding CysCysHisCys (CCHC)-type zinc fingercontaining glycine-rich RNA-binding proteins, designated OsRZ proteins, but their importance and physiological functions remain largely unknown. Here, the stress-responsive expression patterns of OsRZs were assessed, and the biological and cellular functions of OsRZs were evaluated under low temperature conditions. The expression levels of the three OsRZs were up-regulated by cold stress, whereas drought or high sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 31 publications
(98 reference statements)
2
55
0
Order By: Relevance
“…AtGRP7 is abundantly expressed in guard cells and is important for regulating stomatal movement during dehydration and salt stress . GRPs have been shown to function as RNA chaperones during adaptation to cold stress in both monocots and dicots (Kim et al, 2009;. These studies exemplify the myriad functional roles of plant RBPs during normal plant development and in response to environmental perturbations.…”
Section: Introductionmentioning
confidence: 89%
“…AtGRP7 is abundantly expressed in guard cells and is important for regulating stomatal movement during dehydration and salt stress . GRPs have been shown to function as RNA chaperones during adaptation to cold stress in both monocots and dicots (Kim et al, 2009;. These studies exemplify the myriad functional roles of plant RBPs during normal plant development and in response to environmental perturbations.…”
Section: Introductionmentioning
confidence: 89%
“…We have also shown that AtRZ-1a affects negatively seed germination and seedling growth of Arabidopsis under salt or dehydration stress [25]. In recent, the functional roles and RNA chaperone activity of OsRZ proteins in Oryza sativa have been determined during cold adaptation process [26].…”
Section: Introductionmentioning
confidence: 98%
“…One GRP family member, designated RZ proteins, harbors CCHC-type zinc knuckles between the RRM and the glycine-rich region. The functional roles of RZs in plant response to different stresses have been determined in diverse plant species, including Arabidopsis thaliana Kim and Kang 2006;Kim et al 2007aKim et al , 2010a and rice (Oryza sativa) (Kim et al 2010b). In particular, certain family members of RZs have been determined to exert their roles by acting as RNA chaperones (Kim et al , 2010b.…”
Section: Introductionmentioning
confidence: 99%